Molecular to global photosynthesis - Archer, Mary D.; Barber, J. 1940- (Imperial College Press ; Distributed by World Scientific Pub. Co., 2004)
Green plants and photosynthetic organisms are the Earth's natural photoconverters of solar energy. In future, biomass and bioenergy will become increasingly significant energy sources, making a contribution both to carbon dioxide abatement and to the security, diversity and sustainability of global energy supplies. In this book, experts provide a series of authoritative chapters on the intricate mechanisms of photosynthesis and the potential for using and improving photosynthetic organisms, plants and trees to sequester carbon dioxide and to provide fuel and useful chemicals for the benefit of man.
Keywords: Photosynthesis.; Energy crops.; elektronické knihy; electronic books